In vitro evaluation of the effects of various additives and polymers on nerve growth factor microspheres. (8th April 2013) - Sun, Huayan; Xu, Fenghua; Guo, Daihong; Liu, Guiyang
Abstract: Objective : To evaluate the effects of various additives or polymers on the in vitro characteristics of nerve growth factor (NGF) microspheres. Materials and methods : NGF microspheres were fabricated using polyethylene glycol (PEG), ovalbumin (OVA), bovine serum albumin (BSA) or glucose as protein protectors, and poly(lactide- co -glycolide) (PLGA) or poly(lactic acid) (PLA)/PLGA blends as encapsulation materials. Results : Encapsulation efficiencies of the NGF microspheres with various additives or polymers were not more than 30%. A comparative study revealed that OVA was somewhat superior over others, and was thus chosen as the protective additive in subsequent experiments. Polymer analysis showed that NGF release from 1:1 PLA (η = 0.8):PLGA (75/25, η = 0.45) microspheres lasted for 90 d with a burst release rate of 12.7%. About 40% of the original bioactivity was retained on the 28th day, while 10% was left on the 90th day. Discussion and conclusion : The combination of OVA as an additive and the PLA/PLGA blend as the coating matrix is suitable for encapsulation of NGF in microspheres for extended release.